PRELIMINARY EVALUATION OF THE USE OF EDLINK AND SIAKAD LEARNING MANAGEMENT SYSTEMS AS THE BASIS FOR DEVELOPING A MOODLE- AND GATHER.TOWN-BASED LMS FOR CIVIC EDUCATION - Mardianti, Desi; Kusumawati, Intan; Febriana, Rina; Sukaji, Sukaji; Zihni, Faris Hazmi Qaedi; Dartin, Herlina (STKIP Pesisir Selatan, 2025)
Online learning requires the utilization of Learning Management Systems (LMS) that are not only administratively functional but also support the enhancement of students’ digital literacy. This study aims to evaluate the use of existing LMS platforms, namely EdLink and SIAKAD, as the foundation for the subsequent design and development of a Civic Education LMS. A mixed-methods descriptive approach within the initial stages of a Research and Development (R&D) model was employed. Data were collected through questionnaires administered to 20 students and in depth interviews with 4 students focusing on accessibility, interactivity, user interface design, and instructional support. The evaluation results indicate that, overall, EdLink and SIAKAD scored highly in terms of accessibility and administrative management but remain limited in discussion forum interactivity, notification quality, and interface design. These findings highlight the need for designing a more adaptive and interactive Civic Education LMS integrating gamification and artificial intelligence features. This research serves as a preliminary foundation for subsequent expert validation and student trials in the development of the new LMS.